Characterization of Zno:Al Nanolayers Produced by ALD for Clean Energy Applications - Marek Szindler; Magdalena Szindler; Krzysztof Matus; Błażej Tomiczek; Barbara Hajduk (Energies)
The rising demand for sustainable energy solutions has spurred the development of advanced materials for photovoltaic devices. Among these, transparent conductive oxides (TCOs) play a pivotal role in enhancing device efficiency, particularly in silicon-based solar cells. However, the reliance on indium-based TCOs like ITO raises concerns over cost and material scarcity, prompting the search for more abundant and scalable alternatives. This study focuses on the fabrication and characterization of aluminum-doped zinc oxide (ZnO:Al, AZO) thin films deposited via Atomic Layer Deposition (ALD), targeting their application as transparent conductive oxides in silicon solar cells. The ZnO:Al thin films were synthesized by alternating supercycles of ZnO and Al2O3 depositions at 225 °C, allowing precise control of composition and thickness. Structural, optical, and electrical properties were assessed using Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray Spectroscopy (EDS), Transmission Electron Microscopy (TEM), Raman spectroscopy, spectroscopic ellipsometry, and four-point probe measurements. The results confirmed the formation of uniform, crack-free ZnO:Al thin films with a spinel-type ZnAl2O4 crystalline structure. Optical analyses revealed high transparency (more than 80%) and tunable refractive indices (1.64 ÷ 1.74); the energy band gap was 2.6 ÷ 3.07 eV, while electrical measurements demonstrated low sheet resistance values, reaching 85 Ω/□ for thicker films. This combination of optical and electrical properties underscores the potential of ALD-grown AZO thin films to meet the stringent demands of next-generation photovoltaics. Integration of Zn:Al thin films into silicon solar cells led to an optimized photovoltaic performance, with the best cell achieving a short-circuit current density of 36.0 mA/cm2 and a power conversion efficiency of 15.3%. Overall, this work highlights the technological relevance of ZnO:Al thin films as a sustainable and cost-effective alternative to conventional TCOs, offering pathways toward more accessible and efficient solar energy solutions.